Knowledge regarding immunization among mothers of under-five children in Uttarakhand - Kumar, Chandan; Bijalwan, Surbhi; Panwar, Askansha; Joshi, Lumbini; Aswal, Ishita; Aswal, Shalini; Gupta, Priya; Edward, Angel; Gusain, Ritika; Dhondup, Tenzin; Uniyal, Ayush; Pundir, Namrata (International Journal Of Community Medicine And Public Health, 2024)
Background: Immunization is one of the most impactful and cost-effective health investments globally that helps in reducing the burden of infectious diseases keeping children safe. Mothers are the major role players with regard to their children’s immunization. Methods: A descriptive cross-sectional study was conducted to assess knowledge regarding immunization among mothers of under-five children in the Doiwala block of Dehradun, Uttarakhand. A total of one hundred mothers of under-five children were conveniently selected through door-to-door survey. A structured knowledge questionnaire on under-five immunization was administered through the interview technique to assess the knowledge of the mothers. Results: Among 100 mothers of under-five children 13% had poor knowledge, 63% had average knowledge and 24% had good knowledge regarding under-five immunization. There was significant association between age, education status and socioeconomic status of mothers with knowledge score regarding under-five immunization. Conclusions: There is a strong need to increase awareness and knowledge about immunization among children; its benefits and importance. There is also a need to educate people especially mothers regarding harmful consequences of incomplete immunization of children.